THE AMMATOAN WOMEN’S AGENCY THROUGH EARTH-SPIRITUALITY RELATIONS - Zulfikarni Bakri; Muhammad Takbir; Reskiyanti Nurdin (Balai Penelitian dan Pengembangan Agama Makassar, 2026)
Indigenous women's environmental knowledge often operates outside formal governance structures,raising questions about alternative forms of ecological stewardship. This ethnographic study examines howthe Ammatoan women in Kajang, South Sulawesi, exercise environmental authority through the Andingingiritual despite political marginalization. This study used a qualitative descriptive approach, utilizingethnographic data collected during the preparation and conduct of the Andingingi ritual. The data werecollected at the research site through ethnographic fieldwork conducted between December 2024 andFebruary 2025. This research analyzed women's spiritual practices as environmental governancemechanisms. Women assume central authority as ritual coordinators who manage environmentalprotection through spiritual mediation with ancestral, natural, and Tu Riek Akrakna entities. Their rolesdemonstrate environmental governance through